DETERMINAN KINERJA PENYELENGGARAAN PEMERINTAH DI INDONESIA: STUDI EMPIRIS PERANAN KEMANDIRIAN DAERAH DAN KEKAYAAN DAERAH - Muhtar (MANAJEMEN DEWANTARA, 2023)
This study aims to analyze the influence of regional financial factors consisting of independence and regional wealth on the performance of local governments in Indonesia. This study used secondary data from authorized government institutions with a final sample of 506 local governments which were analyzed using multiple linear regression methods. The results of the analysis show that in terms of achievements, the average performance of local governments in Indonesia has been good, but there are still issues of disparities between regions that need to be corrected. Meanwhile, the analysis of hypothesis testing through multiple linear regression found a positive effect of regional independence variables on local government performance. Meanwhile, the regional wealth has no significant effect on local government performance. This research has the implication that improving the quality of regional financial management is very important in the implementation of regional autonomy in Indonesia in order to support the achievement of regional performance so that it must be optimized. In this case, the regional government and the central government must synergize through various policies to improve the quality of regional financial management in order to increase independence, fiscal capacity, and optimize assets